EFEKTIVITAS PEMBELAJARAN KONTEKSTUAL DENGAN STRATEGI RELATING, EXPERIENCING, APPLYING, COPERATING, AND TRANSFERRING TERHADAP PEMAHAMAN KONSEP MATEMATIKA - Helmida Fitri (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding of concept is important in the learning of mathematics. The understanding of oncept is a basic ability that must be developed in students. In fact,  the reality found in the field in the class XI IPS SMA Negeri 1 2X11Kayutanam on understanding of math concepts students is still low. The solution to solve the problem is by applying contextual learning with REACT strategy. The purpose of this study is to determine the abbility of understandingof math concepts of students during contextual learning applied with REACT strategy is better than students who are learning conventionally in class XI IPS SMA Negeri 1 2X11 Kayutanam. This type of research is a quasi experiment with the design of the Static Group Design. The Samples of this research are class XI IPS 2 and XI IPS 3. Based on the data analysis it is concluded that understanding of math concepts of students by contextual learning with REACT strategy is better than students that ready conventionally in class XI IPS SMA Negeri 1 2X11 Kayutanam. Keywords – Understanding Mathematical Concept, cooperative learning strategy REACT, Conventional Learning